Impact of weed infestation on projective soil cover changes during the sunflower vegetation period - Shevchenko , M. V.; Olenchenko , A. V. (Man and Environment. Issues of Neoecology, 2025)
Weed infestation is one of the key factors influencing the formation of plant cover in agroecosystems. In the context of sunflower cultivation, projective soil cover varies depending on the intensity of weed competition, especially during critical periods of vegetation.Purpose. To determine the effect of varying levels of weed competition on the dynamics of projective cover in sunflower crops throughout the growing season.Methods. Field experimentation, laboratory-analytical methods, and statistical analysis.Results. An increase in the duration of weed competition led to a consistent reduction in plant biometric parameters (height, leaf area), projective crop cover, and yield. The highest yield was recorded under full-season weed control, which served as the benchmark for evaluating other treatments. Even short-term weed competition caused a notable yield reduction. Extending the weed-free period improved growth indicators but did not fully compensate for productivity losses. The first month of vegetation was identified as the critical competition period. Limiting weed infestation during the first 30–45 days after emergence significantly improved plant growth, leaf area development, and projective soil cover. The most effective projective cover and biomass accumulation were observed when weed competition was entirely eliminated during this early phase—crucial for ensuring full crop development. Weed spread in later stages had a less pronounced impact on plant morphology but impeded harvesting and increased the risk of secondary field infestation. In contrast, prolonged weed competition suppressed crop development, reduced leaf area, and decreased yield.Conclusions. The findings confirm the importance of weed control during critical biomass formation periods to support the soil-protective function of crops and ensure stable production. The proposed approaches can be used to improve sunflower cultivation technologies, taking into account environmental conditions.